Implementation of Work Improvement in Small Enterprises Program Through Participatory Training for Actors Food Sector - Najihah, Khoirotun; Bawamenewi, Mega Aprilyati; Bakara, Bambang Satria (Jurnal Perilaku Kesehatan Terpadu, 2024)
The phenomenon of occupational health and safety (Kesehatan dan Keselamatan Kerja, or K3) implementation has not been widely adopted in the micro, small, and medium enterprise (MSME) sector, as most MSMEs still do not consider occupational health and safety as a priority. Many view its implementation as an expense, which can potentially lead to significant issues. These include challenges related to worker welfare and business conditions, fire safety, financial burdens resulting from work accidents or occupational diseases, and an uncomfortable work environment that diminishes worker motivation. This situation increases the risk of work accidents, occupational diseases, and decreased productivity. All these issues stem from the lack of awareness about occupational health and safety among MSME actors. One effort to encourage the adoption of occupational health and safety practices in MSMEs is through the Work Improvements in Small Enterprise (WISE) program developed by the International Labour Organization (ILO). This program aims to assist MSMEs in improving working conditions and productivity through participatory training. The training is designed to educate MSME actors, fostering a shift from unawareness to awareness of occupational health and safety practices. The purpose of this study is to determine the effectiveness of the Work Improvements in Small Enterprise program through participatory training, analysis, implementation, and evaluation of MSME actors. This research adopts a qualitative approach using a case study method to provide a comprehensive description of how the Work Improvements in Small Enterprise program is implemented. The study is based on observation data, surveys, and documentation of various tasks and workplaces within a tofu factory, employing a risk identification approach to analyze and identify control measures for these risks. The findings indicate that various tasks in the tofu factory pose specific hazards. Providing training to tofu factory workers through the Work Improvements in Small Enterprise program has proven effective in addressing these risks. The study concludes that participatory training is an effective solution to mitigate potential hazards, preventing work accidents and promoting safer working conditions.